MODEL PENYELESAIAN KONFLIK KEAGAMAAN: STUDI PENYELESAIAN KONFLIK KEAGAMAAN OLEH FKUB KABUPATEN BANYUMAS - Asyhabuddin Asyhabuddin (Jurnal Penelitian Agama, 2020)
This research found that FKUB of Banyumas Regency used a model of conflict manajement to minimize and stop violence driven by religious conflict. This is a very strategic choice because this model of conflict management doesn't take high intensity and a long time to minimize the conflicts and victoms of violence. There are five considered factors of this choice. (1) FKUB is a government-made institution, whose steps to keep the harmonious relationship and prosperity among people of different religions are based on a regulation issued together by some ministers (Peraturan Bersama Menteri). (2) The leaders and members of FKUB are leaders of religious communities that have other job and responsibility. It sometimes prevnt them to totally concentrate on handling problems related religion-based violence that takes long time to solve. (3) FKUB doesn’t have structures on the root level, which directly have a contact with the most basic society. (4) FKUB doesn't have permanent workers who are professionals in conflict management. (5) FKUB doesn't have much budget to handle all its complicated tasks and it causes the difficulty to recruit professionals of conflict management.